2020
DOI: 10.1016/j.nedt.2019.104272
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of an evidence-based model of mentoring nursing students in clinical practice

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 48 publications
3
33
0
2
Order By: Relevance
“…Students make follow-up plans for nursing care based on evidence-based practice following the problems found. Educational interventions to improve the competence of mentors must be designed 16,25,26 . Evidence-based practice is very important for nursing education because Florence Nightingale is a pioneer of evidence-based practice and technology is a key component of the evolution of evidence-based practice 27,28 Diagnostic procedures that were analyzed included abnormal values of cardiac output, fluid balance, acidbase, blood chemistry, IWL, mean arterial pressure, fluid balance, and CBC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students make follow-up plans for nursing care based on evidence-based practice following the problems found. Educational interventions to improve the competence of mentors must be designed 16,25,26 . Evidence-based practice is very important for nursing education because Florence Nightingale is a pioneer of evidence-based practice and technology is a key component of the evolution of evidence-based practice 27,28 Diagnostic procedures that were analyzed included abnormal values of cardiac output, fluid balance, acidbase, blood chemistry, IWL, mean arterial pressure, fluid balance, and CBC.…”
Section: Discussionmentioning
confidence: 99%
“…Satisfaction increased significantly in satisfaction surveys that were routinely collected over one year related to the curriculum by providing material related to evidence-based nursing practice 15 . The results of previous studies show that overall, there is no significant difference between groups with e-learning and conventional learning or face-to-face relating to the knowledge, skills, and satisfaction of nursing students, and also E-learning can be used in offering alternative education method [15][16][17] . The study uses an e-learning model with a journal sharing approach to work on nursing care reports, measure competence, and exam results in critical nursing periods.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire included 12 background questions and the Mentors´ Competence Instrument (MCI) 16,19 . The background questions covered areas such as education, unit of work, work experience and mentor tasks.…”
Section: Methodsmentioning
confidence: 99%
“…The mentor needs to offer students opportunities to develop their cognitive, psychomotor and affective skills, all of which are essential in facilitating the transition from student to healthcare professional 1,2,16 . Previous research has identified several mentor characteristics, (eg positive attitude, effective communication skills, commitment, ability to listen to students), that positively affect students’ learning experiences and adaptation to professional practice 5 …”
Section: Introductionmentioning
confidence: 99%
“…Positive role modelling and work-based mentoring have been shown to strengthen the context and culture of learning, support the learning process and enhance overall learning outcomes. 24,25 Horsburgh and Ippolito (2018) provide useful insights to the value of positive role models and mentors in clinical contexts. Characteristics valued by students was the presence of a role model and/or mentor who is present and involved, has aligned values, engaged in meaningful reflection, provides time for a student to write things down, give abundant opportunity for practice, and provides feedback.…”
Section: Role Modelling and Mentoringmentioning
confidence: 99%